1992
DOI: 10.1038/bjc.1992.175
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence distribution and photodynamic effect of ALA-induced PP IX in the DMH rat colonic tumour model

Abstract: Summary Aminolaevulinic acid (ALA) is the first committed step in haem synthesis. In the presence of excess ALA the natural regulatory feedback system is disrupted allowing accumulation of protoporphyrin IX (PP IX) the last intermediate product before haem, and an effective sensitiser. This method of endogenous photosensitisation of cells has been exploited for photodynamic therapy (PDT). We have studied the fluorescence distribution and biological effect of induced PP IX in normal and tumour tissue in the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
118
2
3

Year Published

1996
1996
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(132 citation statements)
references
References 17 publications
9
118
2
3
Order By: Relevance
“…PDT with topical ALA application has been used extensively for the selective eradication of human malignant skin tumours Svanberg et al, 1994;Cairnduff et al, 1994;Orenstein et al, 1996). Unfortunately, there are relatively few preclinical studies on the ALA potential for PDT after systemic administration (Peng et al, 1992;Bedwell et al, 1992;Regula et al, 1994). The advantages of ALA-PDT are (1) low systemic toxicity ; (2) endogenous PpIX synthesis and compartmental targeting (mitochondria) for PDT damage (Malik and Lugaci, 1987;Peng et al, 1992; (3) rapid clearance of ALA-induced porphyrins from the body (Bedwell et al, 1992).…”
mentioning
confidence: 99%
“…PDT with topical ALA application has been used extensively for the selective eradication of human malignant skin tumours Svanberg et al, 1994;Cairnduff et al, 1994;Orenstein et al, 1996). Unfortunately, there are relatively few preclinical studies on the ALA potential for PDT after systemic administration (Peng et al, 1992;Bedwell et al, 1992;Regula et al, 1994). The advantages of ALA-PDT are (1) low systemic toxicity ; (2) endogenous PpIX synthesis and compartmental targeting (mitochondria) for PDT damage (Malik and Lugaci, 1987;Peng et al, 1992; (3) rapid clearance of ALA-induced porphyrins from the body (Bedwell et al, 1992).…”
mentioning
confidence: 99%
“…For example, various malignant tissues have an increased porphobilinogen deaminase activity, which converts ALA into porphobilinogen, and a decreased ferrochelatase activity, which converts PpIX into haem (van Hillegersberg et al, 1992). This alteration in enzymatic activities may cause an increased fluorescence in tumour tissue compared with normal tissue after ALA administration (van der Veen et al, 1994;Bedwell et al, 1992). Several normal tissues, especially those originating from ecto-and endoderm may also become photosensitised after exposure to ALA.…”
mentioning
confidence: 99%
“…Several studies, both in vivo and in vitro, have reported encouraging results (Malik and Lugaci, 1987;Fukuda et al, 1989Fukuda et al, , 1992aDivaris et al, 1990;Bedwell et al, 1992;Fijan et al, 1995;Roberts and Cairnduff, 1995;Steinbach et al, 1995;Kriegmair et al, 1996). Selective endogenously generated photosensitization depends on differential cellular rates of synthesis and loss of the porphyrins.…”
mentioning
confidence: 99%